(untitled) (Global Journal of Medical Research, 2023)
Miliary tuberculosis is usually seen in pregnant women with a compromised immune system Recent studies have speculated a plausible immune dysregulation for several months following a COVID-19 infection We report the case of a pregnant women who had COVID infection in the first trimester and miliary tuberculosis with ARDS in the third trimester We presume that the onset of tuberculosis as disseminated disease could be due to a weakened immune system following COVID-19 infection and we hope that this case could shed some light on the risk for infections during the post covid phase in pregnancy